1997
DOI: 10.1128/jb.179.18.5914-5921.1997
|View full text |Cite
|
Sign up to set email alerts
|

The tpl promoter of Citrobacter freundii is activated by the TyrR protein

Abstract: The ability of microorganisms to degrade L-tyrosine to phenol, pyruvate, and ammonia is catalyzed by the inducible enzyme L-tyrosine phenol lyase (EC 4.1.99.2). To investigate possible mechanisms for how the synthesis of this enzyme is regulated, a variety of biochemical and genetic procedures was used to analyze transcription from the tpl promoter of Citrobacter freundii ATCC 29063 (C. braakii). By computer analysis of the region upstream of the tpl structural gene, two segments of DNA bearing strong homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…Under tyrosine-induced conditions, the ␤-galactosidase activity of the cells carrying tutB was 1.3-fold as high as that of the cells not carrying tutB (4,400 against 3,300). The mechanism underlying TyrR-mediated tyrosine induction of tpl has been well established (14,28). These results indicated that introduction of the TutB system actually increased the intracellular level of tyrosine.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Under tyrosine-induced conditions, the ␤-galactosidase activity of the cells carrying tutB was 1.3-fold as high as that of the cells not carrying tutB (4,400 against 3,300). The mechanism underlying TyrR-mediated tyrosine induction of tpl has been well established (14,28). These results indicated that introduction of the TutB system actually increased the intracellular level of tyrosine.…”
supporting
confidence: 54%
“…In a preliminary experiment, we observed that the introduction of pACYC177 carrying the tutB gene into an E. coli strain with the ⌽(tplЈ-Јlac) gene (14) enhanced the tyrosine-induction ratio of tpl by twofold, but neither the phenylalanine-nor the tryptophan-mediated induction ratio was elevated. Since the expression of tpl is positively regulated by the TyrR protein (22) and its coeffectors (three aromatic amino acids), even though the magnitude of activation is quite different among the three ligands (13,28), the above observation implied that the tutB gene might encode a tyrosine transporter. In order to characterize the tutB gene product, an E. coli strain deficient in the uptake of all aromatic amino acids (5) was constructed (MG1655 ⌬aroP mtr24 ⌬pheP ⌬tna ⌬tyrP) and used for transport assays.…”
mentioning
confidence: 99%
“…The regulatory mechanism underlying expression of tpl was investigated by means of the lac reporter system, and it was demonstrated that, at least in E. coli, both the TyrR protein and cyclic AMP receptor protein (CRP) participate in it (23,47). The TyrR protein plays a major role in the regulation of genes that are essential for the biosynthesis, transport, and degradation of aromatic amino acids (1,5,8,23,34,42,47).…”
Section: V67amentioning
confidence: 99%
“…Whereas hexamer formation of TyrR causes repression of aroF and tyrP, the tpl promoter is activated by ligand-mediated hexamerization of TyrR bound to the three distant boxes (Fig. 1A) (2,8,20). Activation of tpl also requires the binding of the aromatic amino acid to the N-terminal ATP-independent site.…”
Section: Vol 190 2008 Notes 8239mentioning
confidence: 99%